Sensory Evoked And Event Related Oscillations In Alzheimer's Disease: A Short Review - Yener, Görsev G.; BAŞAR, EROL (Springer, Van Godewijckstraat 30, 3311 Gz Dordrecht, Netherlands, 2010)
Diagnosis and treatment of Alzheimer's disease (AD) depend on clinical evaluation and there is a strong need for an objective tool as a biomarker. Our group has investigated brain oscillatory responses in a small group of AD subjects. We found that the de novo (untreated) AD group differs from both the cholinergically-treated AD group and aged-matched healthy controls in theta and delta responses over left frontal-central areas after cognitive stimulation. On the contrary, the difference observed in AD groups upon a sensory visual stimulation includes response increase over primary or secondary visual sensorial areas compared to controls. These findings imply at least two different neural networks, depending on type of stimulation (i.e. cognitive or sensory). The default mode defined as activity in resting state in AD seems to be affected electrophysiologically. Coherences are also very valuable in observing the group differences, especially when a cognitive stimulus is applied. In healthy controls, higher coherence values are elicited after a cognitive stimulus than after a sensory task. Our findings support the notion of disconnectivity of cortico-cortical connections in AD. The differences in comparison of oscillatory responses upon sensory and cognitive stimulations and their role as a biomarker in AD await further investigation in series with a greater number of subjects.
Keywords: Oscillations; Event Related; Alzheimer; Dementia; P300; Mild Cognitive Impairment; Theta-Oscillations; Cortical Rhythms; Bipolar Disorder; Brain Dynamics; Visual-Cortex; Phase Synchronization; Epileptic Patients; Memory Task; EEG; salınımlar; Olaya ilişkin; Alzheimer; Bunaklık; Hafif Kognitif Bozukluk; Teta-Titreşimler; Bipolar Bozukluk; Beyin Dinamiği; Görsel Korteks; Epileptik Hastalar; Bellek Görev